Rh‐Complex Supported on Magnetic Nanoparticles as Catalysts for Hydroformylations and Transfer Hydrogenation Reactions. Issue 4 (18th March 2022) - Nasiruzzaman Shaikh, M.; Aziz, Abdul; Shakil Hussain, S. M.; Helal, Aasif
Abstract: Herein, we describe a facile protocol for the phosphine complex of Rh anchored on the ultrasmall magnetic nanoparticles for transfer hydrogenation and hydroformylation reactions. A diphenylphosphino‐ferrocenylethyl amine was conjugated with dopamine hydrochloride to form dop‐Fc, which was then anchored on the surface of magnetic nanoparticles to produce Fe3 O4 @dop‐Fc. The prepared materials were complexed with a Rh precursor as a catalytic center. XRD, FTIR, SEM, TEM, and XPS were used to investigate the structure and its reactivity. Rh‐complexes of Fe3 O4 @dop‐Fc were used to convert terminal olefin to aldehyde using syngas (CO : H2 1 : 1) under pressure, obtaining up to 99% selectivity for branched aldehyde. The wide applicability of the Fe3 O4 @dop‐Fc−Rh construct was tested for the selective transfer hydrogenations of nitroarene and N ‐heteroarene. Particularly, quinoline was quantitatively hydrogenated to 1, 2, 3, 4‐tetrahydroquinoline(py‐THQ) using tetrahydroxydiboron (THDB). Also, the functional group tolerance in the reduction of nitroarene and styrene was evaluated. The robustness of the catalyst was tested by reusing it for multiple cycles. Abstract : A Ferrocenylphosphine‐based Rh complex anchored on magnetic nanoparticles (7–9 nm) was prepared. The reactivity of the catalyst towards olefins hydroformylation, transfer hydrogenation of N‐heteroarene and nitroarene has been evaluated.